IFRS 9 and earnings management: the case of European commercial banks - Nnadi, Matthias; Keskudee, Atis; Amaewhule, Wey (Emerald, 2023)
Purpose This paper examines the impact of International Financial Reporting Standards (IFRS) 9 on earnings management (EM) using data from 2011 to 2019 of 100 commercial banks in Europe. Design/methodology/approach Using data from 2011 to 2019 of 100 commercial banks in Europe, the authors conducted several empirical investigations to test the mediating role of IFRS 9 on earnings manipulation through loan loss provision (LLP) by banks. Findings The result shows that the new accounting standards (IFRS 9) significantly affect the way banks report LLP. This paper provides evidence that non-listed banks in the EU engage in EM through LLP following IFRS 9 but experience less volatility of net income following the adoption. The findings indicate that such behaviour by banks cannot be suppressed by level of audit quality; suggesting that an improvement in accounting standards might not always guarantee accounting quality. Originality/value This finding has some policy implications; and regulators will need to identify additional tools to regulate or supervise EM behaviour.
Keywords: commercial banks; earning management; accruals; loan loss provision; IFRS 9